Socio-demographic Characteristics of Women with Reproductive Tract Infection Attending a Military Hospital (Journal of Armed Forces Medical College, Bangladesh, 2020)
Introduction: Reproductive tract infections (RTIs) are being increasingly recognized as a serious global health problem with impact on individual women and men, their families and communities. RTIs are a group of disease that cause infection of the genital tract and include both those that are sexually transmitted and those that are not. RTIs are a significant cause of morbidity and mortality in both men and women, especially in women of reproductive age.Objectives: To determine the socio-demographic characteristics among women with RTIs attending at gynecology outpatient department, CMH, Dhaka.Materials and Methods: This descriptive cross-sectional study was carried out with a view to find out the socio-demographic characteristics of women with RTIs and their common clinical presentations. The study was conducted among women of reproductive age group of Bangladesh Armed Forces attending at Gynecology OPD, CMH Dhaka, for the period of 1st march to 30th June 2011. A total of 128 women (114 married and 14 were unmarried) were interviewed with the help of structured question and checklist. Data was collected through clinical diagnostic approach made by gynecologists.Results: It was found that highest percentage of respondents (32.8%) were in the age group of 30-34 years, mean age at marriage was 17.79 years. The highest percentage of respondents (46.5%) was married at the age range of 16-18 years. Among the respondents, 89.1% were married and 10.9% were unmarried. The women with higher education level had lower occurrence of RTIs than women with lower education. In relation to status of spouse of married women, RTIs were significantly more among the wife of other ranks. Practice of personal hygiene during menstruation showed safe positive impact on RTIs. It was found that 50% respondents were presenting with vaginal discharge (Leucorrhoea). Most of the causes were vaginitis (38.3%).Conclusion: Study findings indicate that high prevalence of RTIs among women is due to the influence of less educational status, low income and also husband's educational background and employment status.JAFMC Bangladesh. Vol 15, No 2 (December) 2019: 218-220